Ferrocene based organometallic gelators: a supramolecular synthon approach - Sahoo, Pathik; Puranik, Vedavati G.; Patra, A. K.; Sastry, P. U.; Dastidar, Parthasarathi (Soft Matter, 2011)
The supramolecular synthon namely primary ammonium dicarboxylate (PAD) synthon has been exploited to generate a new series of salt based low molecular weight gelators (LMWGs) derived from ferrocenedicarboxylic acid (FDCA) and primary amines Me-(CH2)(n)-NH2 (n = 3-15). While most of the salts are capable of forming gels with DMSO and DMF, nearly all of them show a tendency to form gels with at least one of the solvents studied. Structure property correlation based on single crystal and powder X-ray diffraction data in combination with optical-, scanning-, and transmission-electron microscopy reveals that the supramolecular synthon approach adopted herein for designing LMWGs is indeed useful and allows one to get an easy access to a new series of organometallic gelators.

Multi-walled CNT-induced phase behaviour of poly(vinylidene fluoride) and its electro-mechanical properties - Rath, Sangram K.; Dubey, Sachin; Kumar, G. Sudheer; Kumar, Sanjay; Patra, A. K.; Bahadur, Jitendra; Singh, A. K.; Harikrishnan, G.; Patro, T. Umasankar (Journal of Materials Science, 2014)
A simple two-step process was used to disperse acid functionalizedmulti-walled carbon nanotubes (CNTs) in poly(vinylidene fluoride) (PVDF). While the neat solvent-cast PVDF showed coexistence of alpha- and beta-phases; the composite films exhibited only beta-phase crystals. Further studies on the crystalline behaviour, using differential scanning calorimetry and small-angle X-ray scattering techniques showed an increase in the percentage of crystalline phase with CNT. The network formed by CNTs in the matrix reduced the macroscopic electrical resistivity of composite films. The dielectric constant increased with CNT loading. Further, these composites were investigated for its electromagnetic wave absorbance (EWA) and strain sensing properties. The EWA properties were studied in the X-band (6-12 GHz) region. A maximum of similar to 37 dB reflectivity loss at similar to 9.0 GHz was obtained in a similar to 25 mu m thick PVDF film containing only 0.25 wt% of functionalized CNT. Preliminary studies showed a systematic change in electrical resistance by the application of dynamic bending strain in nanocomposite film. The film also showed a significant improvement in mechanical stiffness owing to efficient stress transfer from matrix to filler, the property desirable for a good strain sensor. In view of the unique combination of EWA and electro-mechanical properties, the nanocomposite films are expected to serve as a multifunctional material for strain sensing in health monitoring as well as in radar absorption.